Osteoarthritis and frailty in elderly individuals across six European countries: results from the European Project on OSteoArthritis (EPOSA). Issue 1 (December 2015) - Castell, Maria; van der Pas, Suzan; Otero, Angel; Siviero, Paola; Dennison, Elaine; Denkinger, Michael; Pedersen, Nancy; Sanchez-Martinez, Mercedes; Queipo, Rocio; van Schoor, Natasja; Zambon, Sabina; Edwards, Mark; et al.
Abstract Background Osteoarthritis (OA) is the most common cause of disability in the elderly. Clinical frailty is associated with high mortality, but few studies have explored the relationship between OA and frailty. The objective of this study was to consider the association between OA and frailty/pre-frailty in an elderly population comprised of six European cohorts participating in the EPOSA project. Methods Longitudinal study using baseline data and first follow-up waves, from EPOSA; 2, 455 individuals aged 65-85 years were recruited from pre-existing population-based cohorts in Germany, Italy, the Netherlands, Spain, Sweden and the United Kingdom. Data were collected on clinical OA at any site (hand, knee or hip), based on the clinical classification criteria developed by the American College of Rheumatology (ACR). Frailty was defined according to Fried's criteria. The covariates considered were age, gender, educational level, obesity and country. We used multinomial logistic regression to analyse the associations between OA, frailty/pre-frailty and other covariates. Results The overall prevalence of clinical OA at any site was 30.4 % (95 % CI:28.6-32.2); frailty was present in 10.2 % (95 % CI:9.0-11.4) and pre-frailty in 51.0 % (95 % CI:49.0-53.0). The odds of frailty was 2.96 (95 % CI:2.11-4.16) and pre-frailty 1.54 (95 % CI:1.24-1.91) as high among OA individuals than those without OA. The association remained when Knee OA, hip OA or hand OA were considered separately, and was stronger in those with increasing number of joints. Conclusions Clinical OA is associated with frailty and pre-frailty in older adults in European countries. This association might be considered when designing appropriate intervention strategies for OA management.